Asceticism and the Pursuit of Death by Warriors and Monks (Revista de Artes Marciales Asiáticas, 2012)
There is a strong connection between martial arts and religious practices in Japan. Martial art practitioners, in an effort to utilize inner energy (ki) and to eliminate fear, often turn to ascetic discipline. Mountain ascetics called yamabushi are known for their extreme, life-threatening training methods. Some of them, after ten years of mental and physical preparation, buried themselves alive, aspiring to become living Buddhas. This is the relatively unknown practice of self-mummification: a tradition that originated with Kukai, the founder of Shingon Buddhism. Approximately twenty individuals in Japan have successfully mummified themselves by means of ascetic discipline and special diets. The frame of mind developed while preparing for their deaths is the same mind-set that warriors strive to attain. Single-minded determination, the complete absence of fear, and the nonexistence of self are demonstrated in the actions of these individuals. These are the same qualities that are found in any master of the martial arts.